Patient perspectives on health in chronic illness (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Medical students need to understand patients’ perspectives about illness and its impact on their lives and family, to evolve as truly socially accountable physicians. Methods: Medical students were assigned in pairs to regularly visit a chronically sick patient over 6 months. They completed a portfolio exploring patient attitudes towards their illness, medication, concerns and beliefs. Themes were coded and portfolios were reviewed independently by two tutors and four students extracting data that matched the themes.  New themes were added during the review.  Data was later compiled and discussed by the team to refine key themes and portfolios were again reviewed to check for frequency.Results: Fifty-eight students interviewed twenty-nine patients with a variety of chronic conditions. Areas identified included the important role of family and community.  A major concern of 18/29 (62%) patients was the impact on the family emotionally, socially and financially of their illness. Other concerns were loneliness (5/29), uncertainty about the illness and deteriorating function.  Spiritual issues were important, together with prayer.  Some patients (7/29) viewed their illness as a punishment or curse and wanted to die. Other patients believed their illness was due to diet, physical or emotional stress, contagion or exposure to environmental factors.  Two believed the oxygen for their COPD was addictive, so restricted its use.Conclusions:  As part of providing patient-centered care in the context of Nepal it is important to explore the level of family and community support available to the patient as well as the current impact on the family.